Education Management in Building a Strong and Sustainable Brand Image - Hindun Maisaroh; M Azka Zulfar Rohman; Alma Vorfi Lama (Business and Applied Management Journal, 2025)
Building a strong and sustainable brand image is a crucial strategy for companies to gain a competitive advantage and foster customer trust and loyalty. A well-established brand image enhances brand recognition while reinforcing consumer engagement and long-term commitment. This article explores essential aspects of building a lasting brand image, ranging from a deep understanding of brand values and identity to the implementation of consistent and authentic communication strategies. Emphasis is placed on continuous innovation, reputation management, and active engagement with target audiences. Through case studies and in-depth analysis, this article discusses the challenges and solutions involved in maintaining a brand image that remains relevant in an ever-evolving market landscape. The findings of this research highlight the significance of social skills development, effective communication, and the ability to handle conflicts constructively as critical components in brand sustainability. Social skills play a pivotal role in strengthening brand-community relationships, while effective communication ensures brand messages are consistently conveyed to maintain credibility and trust. Additionally, the capacity to manage conflicts constructively enhances stakeholder engagement and institutional reputation, particularly in the educational sector. This study provides practical guidance and strategic insights for companies and institutions seeking to build a resilient and impactful brand image in today's dynamic environment.